Analysis of Procedures for Procurement of Imported Accessories Products at PT DUA MALAIKAT - Adnen Bait Sabila; Imam Abdul Aziz; Hermawan Hermawan; Raka Imam Rachmawan; R. Arya Rahmadiyatmaka; Rismaya Rismaya; Reni Sulastri; Ricky Firmansyah (Penerbit Jurnal Indonesia, 2023)
This study aims to qualitatively analyze the import procurement procedure in Company PT. DUA MALAIKAT. The research method used is a case study by collecting data from interviews with five respondents involved in the import procurement process. The results show that the import procurement process in Company PT. DUA MALAIKAT consists of several stages, namely determining needs, searching for suppliers, negotiating prices and contracts, verifying suppliers, payment and delivery, quality inspection, as well as receiving and storing goods. This study also found several challenges in the import procurement process, such as difficulties in determining the quality of imported products and issues related to international trade regulations. Therefore, Company PT. DUA MALAIKAT needs to improve import procurement management and collaborate with international trade experts to ensure an effective and efficient import procurement procedure.